Efficacy assessment of oral and sublingual sedation using alprazolam in implantology surgical procedures - Antonio José Bittencourt da ROSA1; Bruno Salles SOTTO-MAIOR2; Carlos Eduardo FRANCISCHONE3; Juliana Cama RAMACCIATO4; Rui Barbosa de BRITO JÚNIOR5; Rogério Heládio Lopes MOTTA4 (Faculdade São Leopoldo Mandic, 2019)
Objective: The aim of this study was to evaluate the efficacy of two formulations of alprazolam (ALP) in patients undergoing oral implantology surgical procedures. Methods: A single-blinded randomized clinical study was performed with 52 volunteers (both genders) divided into 2 groups: G1 (n = 26) - oral administration of ALP (0.5 mg) 1h before surgical procedures; and G2 (n = 26) - sublingual administration of ALP (0.5mg) 30 minutes before surgery. Blood pressure (BP) and heart rate (HR) were evaluated. Corah dental anxiety scale (COR), visual analogic scale (VAS), Trieger test (TRI) and the perception questionnaire (PQ) were used to assess the level of anxiety and responses to formulations, respectively. All parameters were evaluated at three times (be-fore, during and postoperative). Results: For BP and HR no statistically significant differences were observed between periods for G1 and G2 (p> 0.05). For COR, most volunteers were classi-fied such as anxious or very anxious. For VAS, decreased anxiety was significant (p< 0.05) and no statistically significant differences between the two groups both in the period "pre" (p= 0.18) and "post" (p= 0.12) were observed. For TRI, there were no significant differences between the periods considering the number of points lost (p> 0.05). The anxiety reduction was significant (p< 0.05) for both formulations. As for PQ, both formulations showed good volunteers' acceptance (p> 0.05), and they have not reported anterograde amnesia. Conclusion: It was concluded that both formulations were effective for sedation of the evaluated volunteers.